Gandhi: a march to the sea - McGinty, Alice B.; Gonzales, Thomas; illustrator (Las Vegas, NV : Amazon's Children Publishing, 2013)
Recreates Mohandas Gandhi's 24-day March to the Sea, from March 12 to April 5, 1930, which became a pivotal moment in India's quest to become an independent country no longer ruled by Great Britain.
Keywords: Gandhi, Mahatma (1869-1948); Gandhi, Mahatma (1869 - 1948)--Juvenile literature; India--Politics and government--1919-1947--Juvenile literature; Civil disobedience--India--Juvenile literature